Contribución dosimétrica de los órganos de la biocinética del corazón, utilizando el tc99m y ti 201 en el estimado de dosis para adultos, con el diseño de un algoritmo en matlab - Morales Nizama, Rosa Adela (2013)
In internal dosimetry contribution and the significance of the dose of the radiopharmaceutical depends heart and biokinetics. Knowing the importance of the contribution offered the organ’s dose of the biokinetics as radiopharmaceuticals used for diagnostic, it has become a topic fairly specific within the internal dosimetry since the various organs of the human have specific physical and biological properties and this takes to have to be made a greater analysis before selecting the radiopharmaceutical for diagnostic, this mainly depends of the patient. This research consists to analyze and compare to what extent the radiation deposited in the organs source of the biokinetics of the heart contributes to the algorithm designed in Matlab. Our main objective is to design an interphase in Matlab using the Mird formalism and the representation of Cristy-Eckerman to consider the absorbed autodosis of the heart of an adult when is used Tc 99m (Tetrofosmin) and Tl 201 and also the dosimeter contributions of the organs of the biokinetics of the Tc99m and Tl 201. In both contributions dosimetric radiopharmaceuticals in organs of the biokinetics of their respective emissions are significant in the estimated absorbed dose for the adult heart male with highest percentage of contribution of dose of the organs of the biokinetics of the Tc 99m compared to Tl 201. While analyzing how affects these results; If the patient had other diseases, additional myocardial disease